The Impact of Mobile Devices on Traffic in the Cities of São Paulo, Rio de Janeiro, and Recife (Brazil) - Marino, Filipe Ungaro; Kanitz, Marcela; Andrade, Victor; Sandrini, Rafael Takagui; Lucena, Jéssica (National Journal of City Management, 2024)
This study examines the interaction between urban mobility and technology, observing the use of portable electronic devices, such as cell phones and headphones, by drivers, motorcyclists, cyclists and pedestrians in the cities of São Paulo, Rio de Janeiro, and Recife. This research aims to collect data on the frequency of use of these devices and perceptions related to the risks involved. A survey in São Paulo complemented the counts, exploring the habits and behaviors of the different users of the highway or road system. The results indicate that despite technological advances pedestrians and cyclists continue to be the most vulnerable groups in traffic. This study highlights the need for public policies that address this new state of affairs and proposes a critical analysis of any risk-mitigating strategies, with an emphasis on the principles of Vision Zero, seeking to promote safer and more inclusive urban mobility. The article is structured into five sections, ranging from the literature review to the conclusions.
Keywords: Urban mobility; Road safety; Mobile devices